Big data phenotyping in rare diseases: some ethical issues - Hallowell, N; Parker, M; Nellaker, C (Springer Nature, 2018)
Phenotyping based on the analysis of photographic images is refining the categorisation of rare genetic disorders1. Through the development of facial recognition technology incorporating machine learning algorithms (MLAs) this big data approach to phenotyping – computational phenotyping - provides statistical support for determining causative variations and enables patient “matchmaking” for ultra-rare or currently unknown disorders